2018
DOI: 10.17957/ijab/15.0527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sub-Lethal Concentration of Cypermethrin on Histopathological and Hematological Profile of Rohu (Labeo rohita) during Acute Toxicity

Abstract: The present investigation was designed to understand the lethal effects of Cypermethrin (CYP); an active pyrethroid, a widely used against an extensive range of pests in agriculture. In this study, Rohu (Labeo rohita Hamilton) was subjected to the treatment with three sub-lethal concentrations (0.50, 1.00 and 1.5 ppb) of CYP for a total period of 96 h. The results obtained indicated significant stress in the studied fish due to pesticide intoxication. Pronounced effects of CYP on fish hematology included signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…Glucose is the major source of energy and its higher level in plasma act as a stress indicator in present study significant increase in glucose level observed. Our results was in line with findings of (Khan et al 2018) and (Ghayyur et al 2019). Changes in creatinine level shows kidney dysfunction, in present study level of creatinine increased in fish exposed to agrochemical in comparison to control group which may be due to oxidative damage.…”
Section: Discussionsupporting
confidence: 92%
“…Glucose is the major source of energy and its higher level in plasma act as a stress indicator in present study significant increase in glucose level observed. Our results was in line with findings of (Khan et al 2018) and (Ghayyur et al 2019). Changes in creatinine level shows kidney dysfunction, in present study level of creatinine increased in fish exposed to agrochemical in comparison to control group which may be due to oxidative damage.…”
Section: Discussionsupporting
confidence: 92%
“…Pesticides exposed to fish at lethal concentrations of EMB expressed abnormal behaviour like lethargy, rapid opercular movement, loss of balance, excess mucus secretion, and darkening on the body surface. However, no visible symptom was observed in the fish exposed to EMB during the sub-lethal toxicity test for a period of 72 h. In an earlier study, erratic and irregular swimming movements, loss of balance, sudden overexcitability were observed at 0.093 mg L −1 of malathion in rainbow trout [ 46 ]; rapid swimming, higher opercular movements were noticed in cypermethrin treated L. Rohita [ 47 ]; erratic behaviour with sluggish swimming patterns, loss of balance and elevation of opercular respiration in C. carpio exposed to glyphosate [ 48 ]. EMB and abamectin induced hypoactivity in Danio rerio , Zebrafish [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, significant elevation in leukocyte count was observed, consistent with the findings of Velmurugan et al (2016) in Anabas testudineus and with Adhikari et al (2004) in Labeo rohita. This substantial increment could be ascribed to general immune response and defense against Cypermethrin (Khan et al 2018). It is difficult to perform a meaningful comparative evaluation of the effect of Cypermethrin on the hematological profile of fish because of the variability of concentrations used, the period of exposure, and the fish species.…”
Section: Discussionmentioning
confidence: 99%